2020
DOI: 10.1177/0022034520907341
|View full text |Cite
|
Sign up to set email alerts
|

From Beyond the Pale to the Pale Riders: The Emerging Association of Bacteria with Oral Cancer

Abstract: Oral cancer, predominantly oral squamous cell carcinoma (OSCC), is the eighth-most common cancer worldwide, with a 5-y survival rate <50%. There are numerous risk factors for oral cancer, among which periodontal disease is gaining increasing recognition. The creation of a sustained dysbiotic proinflammatory environment by periodontal bacteria may serve to functionally link periodontal disease and oral cancer. Moreover, traditional periodontal pathogens, such as Porphyromonas gingivalis, Fusobacterium nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 91 publications
0
48
0
Order By: Relevance
“…In a plethora of clinical studies, analyses of samples from OSCC patients have revealed significant differences in microbiome composition and function between tumor and control samples, with certain taxa quite consistently showing association with OSCC across studies (Perera et al, 2016 ; Al-Hebshi et al, 2019 ). Of these, Fusobacterium nucleatum and Porphyromonas gingivalis have received the most attention, with large number of studies that characterized their carcinogenic properties in vitro and in in vivo models (Fitzsimonds et al, 2020 ). However, in focusing on exploring the role of species that are enriched in the tumors, i.e., the pathobionts, researchers seem to have largely ignored the health-associated species that in fact may be playing a protective role against oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In a plethora of clinical studies, analyses of samples from OSCC patients have revealed significant differences in microbiome composition and function between tumor and control samples, with certain taxa quite consistently showing association with OSCC across studies (Perera et al, 2016 ; Al-Hebshi et al, 2019 ). Of these, Fusobacterium nucleatum and Porphyromonas gingivalis have received the most attention, with large number of studies that characterized their carcinogenic properties in vitro and in in vivo models (Fitzsimonds et al, 2020 ). However, in focusing on exploring the role of species that are enriched in the tumors, i.e., the pathobionts, researchers seem to have largely ignored the health-associated species that in fact may be playing a protective role against oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyromonas gingivalis lipopolysaccharides could deregulate tumor suppressor gene p53 [72,77]. Gingipains and cysteine proteinases produced by Porphyromonas gingivalis, play a key role in activating MMP-9, which degrades the basement membrane and the extracellular matrix, promoting carcinoma cell migration and invasion, thus allowing dissemination and metastatic growth at remote sites [72,77,78,80]. Also in oral squamous cell carcinoma cells, Porphyromonas gingivalis stimulates the release of a variety of cytokines, including IL-8, which can increase MMP-9 production and cell proliferation and invasiveness [80].…”
Section: Periodontal Bacteria In Carciongenesis -Porphyromona Gingivalismentioning
confidence: 99%
“…B7-H1 expression promotes the event of regulatory T cells that suppress effector T cells. B7-H1 expression might contribute to immune evasion by oral cancers [47,77,80].…”
Section: Periodontal Bacteria In Carciongenesis -Porphyromona Gingivalismentioning
confidence: 99%
“…The structural and functional characteristics of the human oral microbiome in connection with dental caries, periodontitis, or medication-related osteonecrosis of the jaw are reported (de Jesus et al 2020;Kim and Koo 2020;Matsha et al 2020;Williams et al 2020). In addition, the special issue considers evidence that the oral microbiome is involved in oral cancer (Fitzsimonds et al 2020;Hong et al 2020;Wang et al 2020) and diabetes mellitus (Kumar et al 2020;Matsha et al 2020). The microbiome includes microbial eukaryotes and archaea, and it is important that these are not overlooked (Belmok et al 2020;Hong et al 2020).…”
Section: Editorialmentioning
confidence: 99%